Trends in social inequalities for premature coronary heart disease mortality in Great Britain, 1994–2008: a time trend ecological study. Issue 3 (18th June 2012) - McCartney, David; Scarborough, Peter; Webster, Premila; Rayner, Mike
Abstract : Objective: To compare trends in metrics of socioeconomic inequalities in premature coronary heart disease (CHD) mortality in Great Britain. Design: Time trend ecological study with area-level deprivation as exposure. Setting: Great Britain, 1994–2008. Participants: Men and women aged younger than 75 years. No lower age limit. Interventions: None. Main outcome measures: CHD mortality rates. Results: There has been a decrease in socioeconomic inequalities in CHD mortality in absolute terms but an increase in relative terms. CHD mortality rates in men aged younger than 75 years fell by 69 per 100 000 (95% CIs 64 to 74) in the least deprived quintile and by 92 per 100 000 (95% CI 86 to 98) in the most deprived quintile (p for trend: <0.001). Mortality rate ratios comparing the most deprived quintile to the least deprived quintile increased in women aged younger than 75 years from 1.77 (95% CI 1.68 to 1.86) to 2.32 (95% CI 2.14 to 2.52). There was a weak negative association between the average decline of relative rates and area deprivation. Conclusions: It could either be said that inequalities in premature mortality from CHD between affluent and deprived areas have widened or narrowed between 1994 and 2008 depending on the measurement technique. In the context of falling CHD mortality rates, narrowing of absolute inequalities is to be expected, but increases in relative inequalities are a cause for concern.